The Three musketeers ([place of distribution not identified] Digiview Productions, 2004)
This action film features a very young John Wayne and exotic sets filmed right on location. 'The Three Musketeers', bearing but a passing resemblance to the original Alexandre Dumas story, relocates the action to the early 20th century and situates the plot in the Middle East. Wayne sets out to uncover the sinister and diabolical plans of El Shasta (Robert Frazer), and along the way finds himself framed for murder. It's one frantic filled moment after another, as Wayne, joined by his three comedic cohorts, battle to clear his name and expose El Shasta's identity to the authorities.
A modern day take on the classic story by Alexandre Dumas.
John Wayne.
Dolby digital.
In English.
Keywords: Swordplay -- Drama; France -- History -- Louis XIII, 1610-1643 -- Drama